2019
DOI: 10.1200/jco.2019.37.15_suppl.e18291
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and tumor location in patients with desmoid tumors: Data from the desmoid tumor research foundation natural history study.

Abstract: e18291 Background: Desmoid tumors (DTs) are sarcoma, known to invade surrounding tissues, compromising organ function and complications. As few as 5 per 1 million people are diagnosed with DTs annually, which may be an underestimate of the actual affected population due to difficulty in correctly diagnosing the disease. To improve awareness of DTs and better inform treatment development, DTRF, in partnership with the NORD, launched the DTRF patient registry and natural history study. Here, we describe patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…• Misdiagnosis: misdiagnosis is common in rare diseases such as DT [4,6,33]. Based on pathologic similarities with other myofibroblastic diseases (e.g., sarcoma, gastrointestinal stromal tumor, nodular fasciitis, leiomyoma) and the low incidence of DT, 30-40% of DT cases are reported to be misdiagnosed following histologic analysis [33][34][35]. A French nationwide survey demonstrated that one-third of DT are misdiagnosed (the most challenging differential diagnoses are nodular fasciitis and low-grade fibromyxoid sarcoma) [33].…”
Section: Diagnostic Challengesmentioning
confidence: 99%
“…• Misdiagnosis: misdiagnosis is common in rare diseases such as DT [4,6,33]. Based on pathologic similarities with other myofibroblastic diseases (e.g., sarcoma, gastrointestinal stromal tumor, nodular fasciitis, leiomyoma) and the low incidence of DT, 30-40% of DT cases are reported to be misdiagnosed following histologic analysis [33][34][35]. A French nationwide survey demonstrated that one-third of DT are misdiagnosed (the most challenging differential diagnoses are nodular fasciitis and low-grade fibromyxoid sarcoma) [33].…”
Section: Diagnostic Challengesmentioning
confidence: 99%
“…Because of its rarity, DT may be misdiagnosed in as many as 30%–40% of cases, 3,29 resulting in inappropriate or delayed care. In one study, the time from patient‐reported symptom onset to DT diagnosis exceeded one year for 54% of patients 30 . Correctly diagnosing DT is key to optimizing management but, in practice, can prove challenging.…”
Section: Diagnosismentioning
confidence: 99%
“…In one study, the time from patient-reported symptom onset to DT diagnosis exceeded one year for 54% of patients. 30 Correctly diagnosing DT is key to optimizing management but, in practice, can prove challenging. Initial evaluation by a multidisciplinary team with expertise in the management of DT, including medical oncologists, radiation oncologists, radiologists, pathologists, surgeons, and geneticists, is recommended.…”
Section: Symptomsmentioning
confidence: 99%